Impact of financial development on economic growth in the WAMZ: A heterogeneous panel data approach - Ibrahima Diallo; Isatou Mendy (West African Journal of Monetary and Economic Integration, 2017)
This paper investigates the impact of financial development on economic growth in the West African Monetary Zone (WAMZ) from 1990 through 2015 using a Heterogeneous Panel Data Approach. The study made use of Two (2) financial indicators: liquid liabilities of the financial system as a percent of GDP and domestic credit to private sector as a percent of GDP. Economic growth is proxied by the real GDP per capita. Our results show that while liquid liabilities exerts long-run positive impact on economic growth in the WAMZ, the positive impact of domestic credit to private sector on economic growth is not in the long run. At country level, our findings indicate that most countries in the WAMZ could foster long run economic growth through changes in the size of financial institutions. Our findings suggest that structural reforms are needed in order to channel private credit to long run productive and growth-driving sectors
Keywords: C33; G10; O11; O16; 330; Economic growth; Finance; Panel Data; WAMZ